Correlation between leukocyte aggregation score of cerebrospinal fluid and bacterial meningitis in children - Meitha PE Togas (Paediatrica Indonesiana, 2016)
Background Bacterial meningitis is one of life-threatening dis- eases and carries a risk of sequelae in affected children. In terms of cost and rapid differentiation between bacterial and non-bacte- rial meningitis, several tests have been proposed. Objective This study aimed to determine the use of leukocyte aggregation score (LAS) of cerebrospinal fluid (CSF) in diagnos- ing bacterial meningitis. Methods A prospective analytic study was done from October 2001 to July 2002 in the Department of Child Health, Medical School, Sam Ratulangi University/ Manado General Hospital. Children pre- senting with symptoms of meningitis, aged between 28 days and 13 years were enrolled. LAS was counted in percentage. Regres- sion analysis was used to determine the correlation between LAS and diagnosis of bacterial meningitis. Results CSF examinations were done on 35 meningitis patients. Three patients were excluded. The remaining 32 patients com- prised of 11 with bacterial meningitis and the other 21 with non- bacterial meningitis. The mean of LAS in bacterial meningitis was significantly higher than that of non-bacterial meningitis (p<0.001). The cut off value of LAS to diagnose bacterial meningitis was 12.35%. Conclusion LAS may be used as a fast and simple alternative diagnostic tool to confirm the diagnosis of bacterial meningitis